River of darkness - Airth, Rennie, 1935- (Penguin Books, 2005)
Inspector John Madden of Scotland Yard investigates the murder of a family in the post-World War I British countryside. A veteran of the war, Madden immediately recognizes the work of a soldier, but discovering the motive will take longer. First in a series.